IMPLEMENTATION OF SSCS LEARNING MODEL IN IMPROVING STUDENTS’ MATHEMATICS LEARNING MOTIVATION AT CLASS VII.C OF SMPN 4 TAMBANG KAMPAR - Yunasli Yunasli (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper discusses the students’ low mathematics learning outcomes of Class VII.C at SMPN 4 Tambang Kampar Regency. It aims to improve mathematics learning outcomes through the application of the Search Solve Create Share learning model (SSCS) for students at Class VII.C of SMPN 4 Tambang Kampar Regency, which was conducted for 2 months. The research subjects were 32 students at Class VII.C of SMPN 4 Tambang in Kampar Regency. The type of research was classroom action research. The research instrument consisted of learning outcome tests and data collection instruments, which were observation sheets of teacher and student activities. Based on the results of data analysis, the average score of students’ learning motivation in the pre-cycle was 45.0, while the percentage was 35.2%. The average score increased in the first cycle to 60, while the percentage was 46.7%. And the average score increased significantly in cycle II to 100.4, while the percentage was 78.5%. It can be concluded that the application of Search Solve Create Share learning (SSCS) could increase students' learning motivation in mathematics at class VII.C of SMPN 4 Tambang in Kampar Regency.